Analisis Kepuasan Pengguna Gojek dengan Metode Kuantitatif Multimodel - Yulianing Tyas, Sasmi Hidayatul; Muftikhali, Qilbaaini Effendi (Diponegoro University, 2024)
Gojek is the first start-up company in Indonesia to have decacorn status based on CB-Insight's records. With Go-Jek's achievement status being the background factor for satisfaction with Go-Jek application users. This research aims to identify factors that influence Gojek customer satisfaction with application use. In this research, quantitative methods using the EUCS, TAM and Delone and McLean (Multi Model) models were used to identify the independent variables, while the dependent variable was customer satisfaction. The dependent variables in this research consist of Content, Accuracy, Format, ease of use, Timeliness, Perceived Usefulness, System Quality, Information Quality and Service Quality. Quantitative methods were used in this research, based on the calculation results of the GeSCA application. The R-squared value of the model proposed in this study is 0.6922. This means that the independent variables in the model can explain the customer satisfaction variable by 69.22% and the remaining 31.78% is explained by other independent variables that are not in the model. Based on the results of the analysis, it was found that 9 variables had an influence on the customer satisfaction variable, but there was 1 variable that had a significant influence (Service Quality). Conclusion of this research show that the variables Content, Accuracy, Format, ease of use, Timeliness, Perceived Usefulness, System Quality, Information Quality and Service Quality have an influence on user satisfaction.